Early onset, development and histological features of gastric signet-ring cell carcinoma - Wang, Yangkun; Li, Yingying; Wang, Bin; Ran, Dongmei; Zhu, Chaoya; Li, Ping; Jiang, Bo; Wang, Sunan (Frontiers in Oncology, 2023)
Objective: To explore the early onset, development and histological features of gastric signet-ring cell carcinoma (SRCC). Methods: Three hundred and sixty-two patients with differentiated adenocarcinoma with signet-ring cells were enrolled. Histomorphological and immunohistochemical features and patterns of the specimens were observed in detail. Results: Infection of the gastric mucosa, especially by Helicobacter pylori, can cause massive cell proliferation and transformation in the deep gastric foveola, the isthmus of the gastric gland, and the proliferative zone of the upper neck of the gland. Signet-ring-like heterocysts monoclonally proliferated after the redifferentiation and reproliferation, extending horizontally along the gastric foveola. Gastric foveolar-type SRCC grew infiltratively into the lamina propria of the mucosa and the submucosa, signet-ring cells could differentiate into undifferentiated adenocarcinoma with signet-ring cell differentiation, mucinous adenocarcinoma with signet-ring cell differentiation, gastric adenocarcinoma with signet-ring cell differentiation, and fundus gland adenocarcinoma with signet-ring cell differentiation. Conclusion: Early SRCC developed from the proliferative zones of the fundus of the gastric foveola and the neck of the gastric gland, growing horizontally along the gastric foveola. It developed into gastric adenocarcinoma with signet-ring cell differentiation after reproliferation and retransformation in the mucosa.